2018
DOI: 10.1002/advs.201800654
|View full text |Cite
|
Sign up to set email alerts
|

Circular RNA circNOL10 Inhibits Lung Cancer Development by Promoting SCLM1‐Mediated Transcriptional Regulation of the Humanin Polypeptide Family

Abstract: AbstractcircNOL10 is a circular RNA expressed at low levels in lung cancer, though its functions in lung cancer remain unknown. Here, the function and molecular mechanism of circNOL10 in lung cancer development are investigated using in vitro and in vivo studies, and it is shown that circNOL10 significantly inhibits the development of lung cancer and that circNOL10 expression is co‐regulated by methylation of its parental gene Pre‐NOL10 and by splicing factor epithelial splicing regulatory protein 1 (ESRP1). c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
57
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 79 publications
(58 citation statements)
references
References 42 publications
1
57
0
Order By: Relevance
“…circAGFG1 can facilitate the proliferation, migration and invasion of breast cancer cells in vitro and in vivo by regulating the miR-195-5p/CCNE1 axis [15]. circRNA circNOL10 facilitates transcription factor sex comb on midleg-like 1 (SCML1) expression by suppressing transcription factor ubiquitination to inhibit the progression of lung cancer [16]. Several circRNAs were characterized as oncogenes or tumor suppressors in renal RCC [11,[17][18][19]; however, there are still many circRNAs in RCC, and the roles urgently need to be investigated.…”
Section: Introductionmentioning
confidence: 99%
“…circAGFG1 can facilitate the proliferation, migration and invasion of breast cancer cells in vitro and in vivo by regulating the miR-195-5p/CCNE1 axis [15]. circRNA circNOL10 facilitates transcription factor sex comb on midleg-like 1 (SCML1) expression by suppressing transcription factor ubiquitination to inhibit the progression of lung cancer [16]. Several circRNAs were characterized as oncogenes or tumor suppressors in renal RCC [11,[17][18][19]; however, there are still many circRNAs in RCC, and the roles urgently need to be investigated.…”
Section: Introductionmentioning
confidence: 99%
“…CircNOL10 (hsa_circ_0000977) affects mitochondrial function by promoting the expression of the HN polypeptide family in lung cancer (Figure B) . Alterations in mitochondrial function trigger a variety of signaling pathways and ultimately inhibit cell proliferation and cell cycle progression and promote apoptosis in lung cancer cells, thereby significantly inhibiting lung cancer progression . It was found that circPTK2 inhibited transforming growth factor β‐induced mesenchymal‐epithelial transition (EMT) and cell invasion via the miR‐429/miR‐200b‐3p/TIF1γ axis in NSCLC .…”
Section: Tumor‐suppressive Circrnas and Cancersmentioning
confidence: 99%
“…For example, it had been reported that hsa circ 100395 regulated lung cancer cell proliferation, migration and invasion through modulating the miR-1228/TCF21 pathway [45]. Nan et al revealed that circNOL10 could affect mitochondrial function through regulating the humanin polypeptide family and subsequently affect multiple signaling pathways, ultimately inhibiting lung cancer development [46].…”
Section: Discussionmentioning
confidence: 99%